Eksplorasi Metode Penciptaan Seni Rupa Komunitas kentjingandjing Melalui Proyek Seni Rupa Unreasonablenessâ€ Di Kota Malang - Nirwana, Aditya; Andito, Tegar (Studi Budaya Nusantara, 2017)
ABSTRACT "Unreasonableness" art project conducted by starting from some problems faced by the Kentjingandjing, which is (1) The problems of an art exhibition management, which includes issues of funding, human resources, and infrastructure of the arts, (2) public view towards the "function"of art, and (3) artist awareness as a scientist. This projects conducted by implementing scientific methods of art creation, which consists of three stages: 1) Internalization and Incubation of Idea; 2) The formulation of the concept of Creation; and 3) Creation of Art. The conclusion that this activity has effectively become the solution of the issues surrounding the management of art, but to raise awareness of the arts in society, this activity still requires massification, or at least is sustainable activities in which various disciplines can be involved. Besides, the scientific method that implemented in this activity is effective by some of the artists, but some argue the use of methods that 'rigid' like this, would handcuff the idea of creation, in addition to the lack of flexibility for the fluctuations which may occur in the process of artistic creation.